THE PROPHETIC LIFESTYLE AS THE BASIS FOR PHYSICAL FITNESS: A SUSTAINABLE MODEL OF HEALTH IN CONTEMPORARY SOCIETY - Goje, Kabiru (Hamdard Islamicus, 2026)
This paper discusses the Prophetic way of life as a paradigm of general health and physical fitness in the contemporary culture. It also shows the timeless wisdom and applicability of the model by referring to both past knowledge and present applicability. The problem is the growing number of lifestyle-related diseases despite modern medical advancements, which implies that the long-term, value-based health models beyond the conventional medical interventions are required. The aim is to explore how the food habits, sleep, exercise, and habits of the Prophet Muhammad (Øal Allah-u-‘alaihe wa sallam) help to keep them strong, energetic, and physically healthy in the long term. The significance of the subject is that it could offer a culturally informed and spiritually satisfying solution in that it would connect the faith-based practices to the modern preventive health. The qualitative method was applied, and this involved comparative research on recent medical research work on physical health, nutrition and disease prevention and a textual analysis of Hadith literature as well. The results indicate that there is a significant association between the prophetic activities and modern fitness ideas, which focus on prevention, moderation, and balance. In order to promote sustainable health behaviour among diverse individuals, politicians, teachers, and healthcare experts are recommended to consider using prophetic concepts in the mechanisms of wellness.